Measuring the effectiveness of social audits: experiences from Sikkim, India. Issue 2 (17th February 2016) - Tambe, Sandeep; Subba, Ash Bahadur; Basi, Jigme; Pradhan, Sarika; Rai, B. B.
ABSTRACT: India has devolved development funds totalling US46 billion to 240, 000 village self-governments. Social audits are emerging as the main tool to ensure their accountability. This article reports on research that analysed panel data of social audits from 2013 to 2015, along with the evolving policy framework. The research found that irregularities were only in the material component and had declined from 1.74% to 0.40% of expenditure, and that works were being completed at 80% of the sanctioned cost. The article proposes a results framework to measure the effectiveness of social audits that covers their punitive as well as preventive role.